2(3x + 4)-5(2x-3)=7(x-3)+11
Răspunsuri la întrebare
Răspuns de
3
6x+8-10x+15=7x-21+11
-4x+23=7x-10
-4x-7x=-10-23
-11x=-33
x=3
-4x+23=7x-10
-4x-7x=-10-23
-11x=-33
x=3
Răspuns de
3
6x + 8 - 10x +15 = 7x - 21 + 11
6x - 10x - 7x = -21 + 11 -8 - 15
-11x = - 33
x = -33 : - 11
x = 3
6x - 10x - 7x = -21 + 11 -8 - 15
-11x = - 33
x = -33 : - 11
x = 3
Alte întrebări interesante
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă